Blockchain Technology Integration in Halal Supply Chain Management: Examining Trust and Transparency Mechanisms through Institutional Theory Perspective in North Sulawesi - Noho Ulidam; Nur Fitry Latief (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: The halal industry in Indonesia continues to expand, yet supply chain integrity faces critical challenges related to trust, transparency, and verification of Islamic compliance throughout complex distribution networks. Objective: This study examines how blockchain technology can address institutional trust deficits and transparency gaps in halal supply chain management (HSCM) within the North Sulawesi context, grounded in Institutional Theory. Methods: Employing a mixed-methods approach combining quantitative structural equation modeling (SEM-PLS) with 287 respondents from halal-certified enterprises, logistics operators, and certification bodies, alongside qualitative interviews with 24 key informants, this study tests a conceptual framework integrating blockchain's coercive, mimetic, and normative isomorphism mechanisms on supply chain trust and transparency outcomes. Results: Findings demonstrate that blockchain adoption significantly enhances supply chain transparency (β=0.671, p<0.001) and institutional trust (β=0.589, p<0.001), with normative isomorphism emerging as the strongest isomorphic pressure (β=0.542). Smart contract deployment reduced halal verification time by an average of 67% compared to conventional processes. Digital traceability systems improved consumer confidence scores by 43.2%. Conclusion: The study proposes a Blockchain-Enabled Halal Institutional Trust (BEHIT) framework as a novel theoretical contribution, demonstrating that technology-mediated transparency mechanisms function as institutional bridges between religious governance requirements and modern supply chain operations. Practical implications extend to BAZNAS zakat institutions, Islamic banking compliance, and regional halal ecosystem development in Eastern Indonesia.